The multisubset sum problem for finite abelian groups - Muratović-Ribić, Amela (Ars mathematica contemporanea, 2015)
We use a similar techique as in M. Kosters, The subset problem for finite abelian groups, J. Combin. Theory Ser. A 120 (2013), 527-530 to derive a formula for the number of multisubsets of a finite abelian group ?$G$? with any given size and any given multiplicity such that the sum is equal to a given element ?$g$? from ?$G$?. This also gives the number of partitions of ?$g$? into a given number of parts over a finite abelian group.
Keywords: character; composition; finite abelian groups; finite fields; karakter; kompozicija; končne abelske grupe; končni obsegi; particija; partition; polinomi; polynomials; subset sum; vsota podmnožice